Improving The Security Of Steganography In Video Using Genetic Algorithm - et. al., Zahraa Jasim Jaber, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There has been a great development in information technology and methods of sending it via the Internet, but these developments expose the information transferred to violations of its security. To maintain information security, steganography and encryption are used. Hiding technology in multimedia, such as audio, video, text or pictures, provides an ability to protect information. Digital video is one of the most common data embedding media for its high ability to hide sensitive data. Where many methods have been proposed to hide the data in the video to prevent it from being seen by unauthorized persons. This paper proposes a new approach to hiding data in video by using two bitand and bitor processes without using the well-known LSB algorithm in the hiding method. In addition, confidential information is first encrypted using a genetic algorithm by which the encryption key is generated, which increases the strength of the proposed work. The experimental results showed that the used method is effective and safe as it provides a PSNR of 63, which makes the embedding capacity high.